“I’d rather Live in Munich, but my Job in Stuttgart is More Attractive”. Multi-Local Living between Corporate and Spatial Ties - Lisa Garde; Cornelia Tippel (Fuori Luogo)
Previous research has shown that employees with strong corporate ties are less likely to quit. This literature implicitly focuses on people living and working in the same place. But an increasing number of employees live in more than one place, a phenomenon referred to as multi-local living. The aim of this paper is to analyse the corporate ties of multi-local employees working in Stuttgart (Germany) and how such ties influence multi-local living arrangements. The research questions are: 1) Which factors prompted multi-local employees to decide for Stuttgart and their employer? 2) How are strong corporate ties of multi-local employees shaped? 3) And which dilemmas arise from strong corporate and spatial ties to different places and how are they resolved? The study shows that the reasons prompting people to work for an employer in Stuttgart were mostly linked to Stuttgart’s regional specialisation in the tech sector, and that people initially living multi-locally focus on their career capital and future employability. However, while some feel forced to take up their current job and to live multi-locally, for example after only receiving one job offer, others voluntarily decide to take up a job far away from their other place of residence to gain new personal and work-related experience. But it becomes clear that there is a fine line between forced and voluntary multi-local living. Furthermore, this paper focuses on the corporate ties of multi-local employees and their intentions as to whether to remain in Stuttgart with their employer. Employees with low to average corporate ties tend to stay with their employers due to a lack of other job opportunities and would quit if better job opportunities arose. In contrast to the literature on mono-local employees, multi-local employees are more likely to quit, even after having developed strong corporate ties, due to strong spatial ties elsewhere. Decisions on continuing multi-local living arrangements and staying with an employer are complex, depending on the corporate and spatial ties of all household members as well as on future education and job prospects in the respective places. Thus, even strong corporate ties will not prevent employees from quitting if reasons to relocate to the other place of residence dominate. If partners are unable to decide on a common place of residence, some multi-local employees just accept the dilemma and postpone the decision.